الامتثال والانحراف: رؤية تحليلية - ابراهيمي, كوثر; بلوم, محمد (جامعة الوادي University of Eloued, 2018)
تهدف هذه الورقة البحثية للتوصل إلى فهم أوضح للامتثال من خلال التطرق الى مفهوم الانحراف الذي يعكس في ظاهره اختلافا جوهريا يتحدد انطلاقا من خصوصيته كمفهوم معاكس للامتثال، وفي حقيقته تكاملا معرفيا وتداخلا مفاهيميا قد ينتج عنه صعوبة في تحديد طبيعة سلوك الفرد من حيث اعتباره امتثالا او عدم امتثال او انحراف. وان عملية الفصل في ذلك تطلبت منا تفسير سلوكات الفرد وفقا للسياق الذي تتم فيه وطبيعة المعايير التي يتبناها هذا النسق بالمقارنة مع غيره من الأنساق الفرعية أو النسق الكلي. كما أن طبيعة العلاقة بين مختلف هذه الأنساق (انسجام معايير، صراع معايير) تطرح هي الأخرى صعوبة في الحكم على عدم مقبولية سلوك الانحراف عن المعيار أو مقبولية سلوك الامتثال للمعيار. وبذلك فالمقبولية لا تخضع لطبيعة التوجه نحو المعايير الاجتماعية (أي مع أو ضد المعيار)، وإنما تشترط بالضرورة طبيعة المعيار في حد ذاته ونواتج سلوك المتبع له أو المنحرف عنه.ABSTRACT:The aim of this research paper is to understanding of conformity, through the concept of deviance, which reflects in appearance a substantial difference determined by its particularity as a concept opposed to conformity, and, a complementary cognitive in its reality, and, a conceptual overlap that may lead to difficulty in defining the nature of individual behavior from considering it conform, non conform or deviant; and that the division required from us explaining individual behaviors according to the context in which it occurs and the nature of social standards adopted by that social system in comparison to other sub-systems or to the global system. There is also the relationship between these different systems (harmony or conflict of standards) which raises the difficulty of deciding of the acceptance or not of a behavior conforming or deviating from the standard. Therefore, the acceptance are not dependant on the attitude toward social standards (with or against the standard ), but necessarily requires the nature of the standard in itself and the outcomes of the behavior following that standard or deviating from it.
مقال
Keywords: الامتثال ؛ الانحراف ؛ المعايير الاجتماعية ؛ النسق الاجتماعي; Conformity; Deviant; Social standards; Social system